The Hollywood Ten - Berry, John; Hayer, Nicolas (Arrow Films, 2014)
The Hollywood Ten represented a flash point of contention between the governmental body of HUAC and the film industry. These ten men were subpoenaed to appear before the HUAC and each was found to be in contempt of the court and subsequently sentenced to prison because they would not testify for the court. Instead, they used their time in court to challenge the Constitutionality of the court's investigations. Alvah Bessie, Herbert Biberman, Lester Cole, Edward Dmytryk, Albert Maltz, Ring Lardner Jr., Samuel Ornitz, John Howard Larson, Adrian Scott, and Dalton Trumbo all refused to testify for Thomas' Committee and they suffered the consequences. Despite imprisonment and blacklisting, these men and their allies fought for their voices to be heard and oppose the abuses of HUAC against individual rights. In 1950, John Berry directed a 15 minute documentary entitled "The Hollywood Ten" where members of the Hollywood Ten spoke out against civil rights abuse and the blacklisting that had taken place. Hundreds of others in addition to the Ten were blacklisted, but the defiance of these men coupled with their prominence in Hollywood created a media frenzy in response to the case. Some of the Ten eventually kept writing for Hollywood under pseudonyms for reduced pay while others left the country. Of the other entertainers who were blacklisted in the film industry, very few were able to return to their careers at all. [scalar.usc.edu]